Diphenylcyclopropenone for the treatment of cutaneous in‐transit melanoma metastases – results of a prospective, non‐randomized, single‐centre study. (13th July 2017) - Read, T.; Webber, S.; Tan, J.; Wagels, M.; Schaider, H.; Soyer, H.P.; Smithers, B.M.
Abstract: Background: Current treatments for in‐transit melanoma (ITM) metastases are frequently invasive and do not improve overall survival. Recently, there has been increasing investigation into the use of topical agents. Diphenylcyclopropenone or diphencyprone (DPCP) is a novel, topical therapy that has been reported to have immune‐sensitizing properties useful in the treatment of ITM. Objective: To assess the clinical outcomes of patients treated within a prospective, non‐randomized, non‐comparative study using DPCP for cutaneous ITM metastases. Methods: A review was conducted assessing the outcomes of 58 patients prospectively treated using DPCP. Patients had satellite or in‐transit disease (stage IIIB+), with all lesion morphology types included. The patients were treated through a single, specialized clinic with regular outpatient follow‐up. DPCP was topically applied as an aqueous cream in 0.005–1% concentrations once to twice per week for up to 24–48 h of duration. To assess variables associated with response, a per‐protocol statistical analysis was performed. Results: Fifty‐four patients were treated who satisfied eligibility criteria for analysis. The overall response rates were as follows: complete response 22%, partial response 39%, stable disease 24% and progressive disease 15%. The mean time to complete response was 10.5 months, mean duration (disease‐free interval) 12.3 months and recurrence rate in complete responders 41%. Lesion morphology was predictive of clinical benefit with a higher response in epidermotropic disease ( P < 0.05). Conclusions: DPCP provided a well‐tolerated, convenient and efficacious treatment for cutaneous ITM metastases. Identifying patterns of response may assist treatment selection and improve patient‐rated outcomes.